The Effect of Learning Anxiety and Procrastination on Students' Accounting Learning Outcomes in Class X - Sitinjak, Meysie Tasya Ardella; Hanu, La; Darma, Jufri; Sridewi, Tuti; Herliani, Rini (Jurnal Pendidikan, Sains Sosial, dan Agama, 2024)
The issue addressed in this research is the low learning outcomes in accounting, specifically in the subject of general journals, among Class X students at SMKN 1 Medan. The purpose of this study is to determine the effect of learning anxiety on the accounting learning outcomes of Class X students at SMKN 1 Medan, and to assess the impact of procrastination on the same outcomes. This research was conducted at SMKN 1 Medan. The population of this study consists of all Class X AKL students at SMKN 1 Medan, totaling 142 individuals. The sampling technique employed was simple random sampling, re-sulting in a sample size of 105 respondents. Data collection was performed using a questionnaire with a Likert scale. The data were analyzed using Partial Least Square (PLS) analysis with the assistance of SmartPLS software. The tests conducted included PLS Algorithm, Bootstrapping, and hypothesis testing using p-value with a significance level of less than 0.05. The analysis results indicate that all outer loading values are above 0.6 and the Average Variance Extracted (AVE) is above 0.5, demonstrating that construct validity is met. Based on hypothesis testing, learning anxiety has a significant effect on students' learning outcomes, with a p-value of 0.029 (< 0.05), thus the hypothesis is accepted. Similarly, pro-crastination significantly affects students' learning outcomes with a p-value of 0.000 (< 0.05), leading to the acceptance of this hypothesis as well. Therefore, it can be concluded that both learning anxiety and procrastination negatively influence the learning outcomes of Class X students at SMKN 1 Medan